A violência escolar em matérias de jornal: um imaginário construído em Belém-PA - SILVA, Livia Sousa da (Universidade de São Paulo, 2023)
With the intention of investigating the constitution of the imaginary school violence in the media text; believing that the media is full of intentions that construct an imaginary of school violence influencing opinions and decisions, whether in the private or public sphere jurisdiction; participating even in the construction of school violence as an object of study, attention and intervention. That is what we propose in this work, a first incursion into this field of meanings, combining studies of Sociology of Communication and the Imaginary and studies of Comprehensive-Dialogical Hermeneutics, in order to expose a prelude to the framing of this research.